Association of leptin gene polymorphism with 305 days milk - VOHRA, V; CHAKRAVARTY, A K; SINGH, A; GUPTA, I D; CHOPRA, A; DUBEY, P P; KUMAR, D (The Indian Journal of Animal Sciences, 2011)
Leptin protein is synthesized by adipose tissue and is involved in regulation of milk yield. We investigated the association of genetic polymorphism in the bovine leptin gene with 305 days milk yield for the first 3 lactations. The study was conducted on 209 lactating Karan Fries cattle with known pedigree belonging to 3 genetic groups at an organized herd. All the cattle were genotyped by PCR-RFLP assay, and 3 genotypes, viz. TT, TC and CC were identified in the exon-2 region of leptin gene. Representative PCR products of the genotyped animals were sequenced across the polymorphism. Karan Fries cattle with TT genotype showed significantly higher 305 days milk yield as compared to cattle with CC genotype.